Clinical profile of silent cerebral infarction patients - Nishimaru, Katsuya; Nobuhara, Kouji (Japanese Journal of Stroke, 1996)
The purpose of the present study was to evaluate the clinical profile of silent cerebral infarction patients, based on consecutive patients with lacunar lesions detected by cranial CT. From among a series of patients who had undergone CT at Fukuoka University Hospital between January 1983 and April 1989, 3006 patients without apparent lesions on CT were extracted. Of these 294 patients (193 men and 101 women; age, 64.5 ± 12.5 yr. mean ± SD) with lacunar lesions were examined in this study. The subjects were divided into two groups : 164 who had no clinical stroe episodes (silent infarction group) and 130 who had stroke episodes (infarction group). The CT findings and vascular risk factors were compared between the two groups. The number and size of lacunar lesions were smaller in the silent infarction group than in the infarction group. In the silent infarction group, the number of lacunar lesions increased as the age of the patients increased. Among the risk factors, hypertension, values for the hemoglobin, hematocrit, uric acid and total cholesterol levels were found to difer between the two groups. The complication of hypertension and actually measured blood pressure were significantly lower in the silent infarction group than in the infarction group. The values for the hemoglobin, hematocrit, uric acid and total cholesterol in the silent infarction group were lower although within the normal ranges than those in the infarction group. Multivariate analysis suggested that the values of the nematocrit. In the asymtptomatic group, 35.3% of the subjects had no vascular risk factors and involved patients who were diagnosed as having malignant tumors. Our study demonstrated that silent cerebral infarction patients had fewer vascular ris factors as compared to cerebral infarction patients.